Influencia del curado sobre la evolución de la corrosión en vigas de hormigón armado con diferentes agregados finos - Cabrera, O. A.; Ortega, N. F.; Schierloh, M. I.; Traversa, L. P. (Revista ALCONPAT, 2012)
This paper analyses how the type of curing affects concrete microstructures with different fine aggregates in relation to the ingress of fluids closely connected with steel deterioration. Five different groups of specimens and beams of reinforced concrete were evaluated with curing in normal conditions, at laboratory ambient, in muffle furnace, at cold ambient and under wind action. Beams were submitted to accelerated corrosion tests in the presence of chlorides. It was concluded that capillary suction is very sensitive to the type of curing. In beam corrosion, defective curing highly influenced the time of appearance of the first crack, the area and maximum wide of cracks. Keywords: crushed sand; shape and surface texture; reinforced concrete; corrosion; chlorides.